2.2.1. Synthesis, spectroscopic characterization and crystal structure of [ReV(O)2(pyz)4][ReII(NO)Br4(pyz)] (pyz = pyrazine) (Communications in Inorganic Synthesis, 2015)
Abstract: A novel Re(V)-Re(II) nitrosyl complex, [Re(O)2(pyz) 4][Re(NO)Br4(pyz)] (pyz = pyrazine) was prepared and characterized by X-ray diffraction, elemental analysis, infrared and ultraviolet-visible absorption spectra. This product is obtained in the initial steps of the reaction of (NBu4)[Re(NO)Br4(EtOH)] with pyrazine. Both, the cation and the anion are mononuclear complexes. The Re(V) atom in the cation is six-coordinate with four nitrogen atoms from pyrazine ligands, and two oxo ligands. The Re(II) anion is also six-coordinate, with four bromide ligands, a linear nitrosyl group and one nitrogen from pyrazine. The spectroscopic studies are discussed and compared with those already reported separately for the cation and the anion. Supporting information: X-Ray (CIF file)